2009
DOI: 10.1111/j.1939-1676.2008.0270.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Combination Chemotherapy for Treatment of Gastrointestinal Lymphoma in Dogs

Abstract: Background: Chemotherapy for multicentric canine lymphoma has favorable results. The gastrointestinal (GI) tract is the most common extranodal site of canine lymphoma, but there have been no prospective studies to determine outcome when dogs with GI lymphoma are treated with chemotherapy.Hypothesis: Treatment with a multiagent chemotherapy protocol is associated with a poor outcome in dogs with GI lymphoma. Animals: Eighteen dogs with histologically confirmed GI lymphoma. Methods: Prospective clinical trial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
119
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(137 citation statements)
references
References 20 publications
14
119
2
2
Order By: Relevance
“…The overall survival time (487 days) exceeded the longest survival time of a dog with primary GI B-cell lymphoma reported by Rassnick et al (2009) and this despite the lymphoma being histologically confirmed in the stomach, small and large intestine. Despite the negative prognostic indicators, complete clinical remission and long survival was achieved.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The overall survival time (487 days) exceeded the longest survival time of a dog with primary GI B-cell lymphoma reported by Rassnick et al (2009) and this despite the lymphoma being histologically confirmed in the stomach, small and large intestine. Despite the negative prognostic indicators, complete clinical remission and long survival was achieved.…”
Section: Discussionmentioning
confidence: 92%
“…Median survival time is longer for dogs with B-cell GI lymphoma in comparison to those with the T-cell lymphoma, but the difference is not statistically significant (Rassnick et al 2009). Marconato et al (2011) noticed higher complete response rates among dogs with B-cell lymphomas treated with a CHOP-based protocol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations